The proximal femoral universal nail system (PFUN): a novel intramedullary nail for treating complex proximal femoral fractures and its biomechanical comparison with the proximal femoral nail anti-rotation (PFNA) - Fang Zhou; Jixing Fan; Yang Lv (Journal of Orthopaedic Surgery and Research)
Abstract Aims The loss of medial and lateral wall support were the main risk factors of implant failure for proximal femoral fractures. A novel intramedullary nail, called proximal femoral universal nail system (PFUN), was proposed by our team to reconstruct the medial wall and lateral wall integrity and the biomechanical performance was evaluated in this study. Methods The synthetic femora were assigned to three groups randomly according to three different proximal femoral fracture types. For each group, the PFUN or PFNA were implanted separately and divided into PFUN subgroup and PFNA subgroup. Biomechanical tests were separately conducted in the axial compression test, torsional test, and fatigue test in sequence. The finite element analysis (FEA) was conducted by ANSYS 14.5 and we analyzed the von Mises stress distribution and the model displacement of two implant models in three different fracture types. Results For proximal femoral fractures with intact medial wall and lateral wall, our biomechanical results showed that the PFUN had a similar biomechanical property with the PFNA. Furthermore, the biomechanical results showed that the PFUN had a larger axial stiffness, higher torsional strength, and a similar failure load when compared with the PFNA for proximal femoral fracture with medial wall fracture. For proximal femoral fractures with broken medial wall and lateral wall, a larger axial stiffness, higher average torque and higher failure load were found in the PFUN when compared with the PFNA. The FEA results showed that the PFUN model had a higher stress concentration compared with the PFNA model, and the total displacement of the PFNA model increased by 11.63% when compared with the PFUN model in the proximal femoral fracture with broken medial wall and lateral wall. Conclusion Our results showed that PFUN had better biomechanical performance than PFNA, especially for complex proximal femoral fractures with medial wall fracture and lateral wall fracture, indicating that the PFUN had great potential as a new fixation strategy in future clinical applications.